Dampak Penjualan Pakaian Bekas terhadap Tingkat Pendapatan Pedagang di Pasar Sambu Kota Medan Dalam Prespektif Ekonomi Islam - Isma Padillah; Kamilah Kamilah; Muhammad Lathief Ilhamy Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
This review plans to decide the effect of selling utilized garments on the pay level of mercants and what are the supporting and hindering variables in selling utilized garments on the pay levels of dealers in the Medan city Sambu market and to decide the Islamic monetary perspective on the pre-owned garments deal. The exploration utilizes enlightening subjective technique. Research area in Sambu market on Sutomo road, Medan city. Information assortment strategies utilized ae perception, meetings and documentation. The information examination procedure utilized is qualitation information investigation. From the aftereffects of the review, it tends to be inferred that the effect of selling utilized garments on the pay level of dealers is exceptionally persuasive on the financial degree of brokers, utilized attire vendor organizations can make the economy of little networks, and assist the center and lower class with getting marked garments at entirely reasonable costs. The restraining factors in the offer of utilized attire to the pay level of vendors are the Covid-19 pandemic, goverment restrictions and grumblings from clients. What's more whenever saw from an Islamic monetary viewpoint, trading utilized garments in the sambu market is reasonable, in light of the fact that exchanging utilized garments can help the requirements and further develop the economy despite the fact that the public authority with this law disallows the import of utilized garments. Keywords : Sale of used clothes, Income level, Islamic economy